1969
DOI: 10.3171/jns.1969.31.1.0025
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Analysis of Shotgun Injuries to the Central Nervous System

Abstract: HIS is a study of the ballistic characteristics of shotgun injuries to the central nervous system. The usual clinical observation provides no obvious correlation between the degree of injury to the central nervous system and factors such as range of the shot, number of pellets striking the head, size of shotgun, or size of pellet (Fig. 1). Examination of the clinical records of the University of Missouri School of Medicine from 1957 to 1966 revealed 19 shotgun injuries of the head with sufficient information t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…Most of the patients presented with GCS range (9-12) 17 (44.7%) & (13-15) 16 (42.1%)while (5-8) 5 (13.2%), outcome of (13-15) group was the best (87.5%) and it is signi icant factor and has strong positive correlation with the outcome, which is comparable to the studies that showed a postresuscitation GCS score greater than 8was highly predictive of favorable outcome (Sights, 1969;Aarabi et al, 2014;Mark et al, 2010).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Most of the patients presented with GCS range (9-12) 17 (44.7%) & (13-15) 16 (42.1%)while (5-8) 5 (13.2%), outcome of (13-15) group was the best (87.5%) and it is signi icant factor and has strong positive correlation with the outcome, which is comparable to the studies that showed a postresuscitation GCS score greater than 8was highly predictive of favorable outcome (Sights, 1969;Aarabi et al, 2014;Mark et al, 2010).…”
Section: Resultssupporting
confidence: 67%
“…Eleven (31.4%) of the patients had a seizure, and 24 (68.6%) of them were free of seizure. Most of the studies showed a range of 25% -55% of seizure in post-PBI, and as a factor affecting the surgical outcome, it is not signi icant (Sights, 1969;Kim, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…This is represented by the equation ED = E/A (kinetic energy/cross-sectional area of the bullet), where kinetic energy equals (mass × velocity 2 )/2. Based on a previous study, the minimum ED of a BB to penetrate an adult skull is 7 × 10 4 ft•lbs/sq ft. 18 The most common caliber of a BB or pellet is 0.177, which equals a 0.177-inch diameter. BB and pellet weights range from 5.1 to 16.1 grains, where 437.5 grains equals 28.35 g. Using the lowest BB weight (5.1 grains or 0.33 g), adult skull penetration can occur at 1025.9 ft/sec.…”
Section: Discussionmentioning
confidence: 99%
“…Civilian penetrating head injury is a leading cause of morbidity and mortality and represents a significant public health problem. The severity of the injury is related to several factors, including velocity of the bullet, refraction of a bullet after hitting a hard structure, distance of flight, caliber, and trajectory of passage through the cranium, expressiveness of the damaged brain, vascular injury and bullet migration [1][2][3]6,8,10,14,18,[20][21][22][23]25 . This last factor has been noted previously by other authors in the medical literature in the last 30 years.…”
Section: Introductionmentioning
confidence: 99%